Potret Kehidupan Anak Jalanan di Kecamatan Ilir Timur I Kota Palembang - Fitri, Fitri; Hendarso, Yoyok; Waspodo, Waspodo (Mahesa Research Center, 2021)
This study aims to analyze and describe the life of street children located in Ilir Timur I District, Palembang City. This study uses the Weber concept of social action. The method used in this research is qualitative research methods. The design used in this research is exploratory. Data collection methods used in this study are observation, in-depth interviews and documentation. There are 10 informants in this study. The results showed that the causes of the emergence of street children were helping the family economy, meeting personal needs, working habits since childhood, influence from peers / games and disharmony in the family. The life portrait of street children is depicted in three parts, which are seen from the economic, social and educational conditions. Judging from the economic conditions, street children are included in the economic category of the lower middle class. From a social perspective, these street children have a pretty good social relationship with friends and neighbors. But in the family it is not good because the parents and children are busy working. Finally, the education condition of street children is good because there are still children who are in school.